Navigating Challenges in Shared Decision-Making in Danish Patient Care - Hindhede, Anette Lykke; Schumann, Maria Cecilie; Larsen, Kristian (Professions and professionalism, 2025)
Patient-centered care and patient choice are reshaping management practices in the Danish public healthcare sector. Patients are becoming more involved in their treatment and assuming greater control over their healthcare decisions. This transformation redefines relationships among patients, professionals, and the state. It raises important inquiries into how healthcare professionals navigate their new roles and responsibilities within this changing landscape. In this paper, we interviewed ten health professionals to delineate how they handle user involvement in daily clinical practice. Utilizing a sociology of profession framework for thematic analysis, our research revealed the disparities between the ideal and the actual implementation of patient-centered care. It highlighted the challenges healthcare professionals encounter in integrating shared decision-making practices and ensuring patients are adequately informed. We conclude that uncertainties regarding responsibility allocation and the boundaries of healthcare professional involvement often overshadow shared responsibility between healthcare professionals and patients.